Microstructural and Optical Performances of Sol-Gel- Synthesized Nd-Doped ZnO Nanoparticles with Various Nd Contents - He, Haiyan; Lu, Jing (Recent Patents on Materials Science, 2016)
This work presents the manufacture and potential application of the ZnO materials with various cation dopings in recent literature and patent and then focus on the deposition and Nd doping effect of ZnO nanoparticles. The influence of Nd-doping in the range of 0-0.79 at % on microstructural and optical properties of ZnO nanoparticles were studied. X-ray diffraction measurement revealed the formation of single-phase ZnO nanocrystallite with a nanoscale particle size in the range of 36.8-39.5nm. With increasing Nd content, UV-visible light absorbance first decreased and then increased, whereas band gap first widened and then narrowed. The absorbance and band gap show optimal values as Nd content is 0.39 at %. The nanoparticles showed strong visible emission varied with Nd doping due to variation of average particle size. The Nd doping also introduced a new emission center and weakened the visible defect emissions.
Keywords: Nanostructure materials